SIMILARITIES AND DIFFERENCES OF DEGREE OF ADJECTIVE IN ENGLISH AND UZBEK LANGUAGES - Bozorboyeva Madinabonu; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: This research paper aims to explore and compare the degrees of adjectives in the English and Uzbek languages. It examines the similarities and differences in the ways adjectives are used to express varying degrees of comparison, such as positive, comparative, and superlative forms. The study will analyze the grammatical structures, rules, and patterns governing the formation of degrees of adjectives in both languages. By highlighting the linguistic features unique to each language and identifying commonalities between them, this research contributes to a better understanding of the linguistic systems of English and Uzbek. The findings of this study may also have implications for language learners and educators seeking to improve their proficiency in either language.